2014
DOI: 10.1080/01431161.2014.960623
|View full text |Cite
|
Sign up to set email alerts
|

A maximum entropy method to extract urban land by combining MODIS reflectance, MODIS NDVI, and DMSP-OLS data

Abstract: Researchers often encounter difficulties in obtaining timely and detailed information on urban growth. Modern remote-sensing techniques can address such difficulties. With desirable spectral resolution and temporal resolution, Moderate Resolution Imaging Spectroradiometer (MODIS) products have significant advantages in tackling land-use and land-cover change issues at regional and global scales. However, simply based on spectral information, traditional methods of remote-sensing image classification are barely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
34
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 54 publications
2
34
0
Order By: Relevance
“…Numerous studies have indicated that the urban land area in this country exhibited an exponential growth pattern during the past two decades [3][4][5]. This unprecedented phenomenon is accompanied by massive rural-urban migration [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have indicated that the urban land area in this country exhibited an exponential growth pattern during the past two decades [3][4][5]. This unprecedented phenomenon is accompanied by massive rural-urban migration [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…More importantly, problems related to the same objects using different spectra and different objects using similar spectra remain unresolved, which increases the difficulty of distinguishing between urban and bare lands simply based on the spectral information obtained from several bands of surface reflectance data. Furthermore, exploring regional or global areas is labor intensive and time consuming because of the massive data volumes involved [36]. Thus, to precisely and reliably extract urban areas, DMSP-OLS data are used as the main data source of the data integration, and spectral information from the surface reflectance data is only used as an auxiliary source.…”
Section: Introductionmentioning
confidence: 99%
“…Other approaches for species distribution modelling and classification include the Maximum Entropy algorithm (MaxEnt) developed by Phillips et al (2006), which requires a series of occurrence locations and a set of explanatory variables defining features that potentially influence the suitability of a species or an event. MaxEnt has been extensively applied for species distribution mapping (Kumar et al 2014) for one-class classification purposes (Lin et al 2014) and probability distribution in various other fields (Petrov and Wessling 2014). Because MaxEnt has shown higher predictive accuracy for classification problems and distribution modelling than other methods such as SVM and artificial neural networks (ANN) (Lin et al 2014;Phillips et al 2006), it was selected for this study.…”
Section: Introductionmentioning
confidence: 99%
“…MaxEnt has been extensively applied for species distribution mapping (Kumar et al 2014) for one-class classification purposes (Lin et al 2014) and probability distribution in various other fields (Petrov and Wessling 2014). Because MaxEnt has shown higher predictive accuracy for classification problems and distribution modelling than other methods such as SVM and artificial neural networks (ANN) (Lin et al 2014;Phillips et al 2006), it was selected for this study.…”
Section: Introductionmentioning
confidence: 99%